2017
DOI: 10.1177/0956797617695100
|View full text |Cite
|
Sign up to set email alerts
|

The Detrimental Effects of Oxytocin-Induced Conformity on Dishonesty in Competition

Abstract: Justifications may promote unethical behavior because they constitute a convenient loophole through which people can gain from immoral behavior and preserve a positive self-image at the same time. A justification that is widely used is rooted in conformity: Unethical choices become more permissible because one's peers are expected to make the same unethical choices. In the current study, we tested whether an exogenous alteration of conformity led to a lower inclination to adhere to a widely accepted norm (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 34 publications
1
40
1
Order By: Relevance
“…Previous studies have reported that OXT administration only led to increased lying behaviour (compared to PLC) when it benefitted an in-group (including oneself) and in competitive environments, in which participants were concerned that another person would take the money by lying if they did not also do so. But no effects on pure self-serving lying behaviour were observed [6, 7]. This might at first glance seem contradictory to the present results.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported that OXT administration only led to increased lying behaviour (compared to PLC) when it benefitted an in-group (including oneself) and in competitive environments, in which participants were concerned that another person would take the money by lying if they did not also do so. But no effects on pure self-serving lying behaviour were observed [6, 7]. This might at first glance seem contradictory to the present results.…”
Section: Discussioncontrasting
confidence: 99%
“…In the OXT administration studies by Shalvi and colleagues and Aydogan et al [6, 7], coin-toss tasks were used where participants only had two choices: “lie” or “be honest”. In comparison, in the present study participants had more gradations of honesty or lying to choose from.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many prosocial effects of OXT have been reported it has also been found to promote self-serving lying and group-serving dishonesty (Sindermann, 2018, Shalvi & De Dreu, 2014). In addition, OXT’s detrimental effect on honesty was found in a competitive environment and driven by conformity with the behavior of peers (Aydogan, Jobst, D’Ardenne, Müller, & Kocher, 2017). On the other hand, intranasal OXT also tends to increase both altruistic help as well as costly altruistic (altruistic punishment) behaviors (Hu et al, 2016; Aydogan, Furtner, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%